Cross-culture analysis of batik sub-culture Pekalongan: A case study on the complexity dimensions of representation, diversity and conflict - Pratiwi, Oktafiani C.; Marwah, Sofa; Ramadhanti, Wita (Faculty of Social and Political Science, Universitas Airlangga, 2024)
Pekalongan batik sub-culture development is influenced by three cultures namely Javanese, Chinese and Arabic. Most studies of batik use a cultural and socioeconomic analysis by focusing mainly its cultural aspects. This research aims to analysis transformation of social and economic assets, by using a different perspective namely cross-cultural theory and democratization framework in order to explain the political economic contestation among the entrepreneurs. This research uses Robert Dahl's conceptual framework regarding the development of democracy and only uses three of the seven relevant aspects, namely: (a) representation, (b) diversity, and (c) conflict. Case studies as a qualitative methodology are used with in-depth interview techniques, observation and literature reviews as data collection tools. The results of this study are, Pekalongan batik sub-culture has formed a kind of long acculturation formation in the cultural perspective, but secondly it also contributes to develop a kind of political contestation, conflicts and gender-bias political practices This study concludes that regional autonomy and decentralization policies have created space for political contestation and opened up opportunities to transform the social/economic capital of batik entrepreneurs as assets for political contestation and have even raised the issue of identity politics.